Quelques remarques épistémologiques sur l’évolution du « procès de travail » - Jean-Max Noyer (Communication)
The objective of this article is to examine the diffusion of associationist models at the heart of the work and thought processes. Taking as its' starting point an analysis of the profound transformations of memory and writing systems, the author highlights a certain number of characteristics of the evolution of this process. By remaining close to the political/cognitive question concerning the new digital networked memories as well as to research on the process of differentiation of knowledge producing collective dispositifs, he attempts to show the power of these models, and in so far as this is possible, in a critical way.